Comparing the clinical outcomes of laparoscopic sleeve gastrectomy and hiatal hernia repair with or without fundoplication for weight loss and gastrointestinal reflux resolution - Al Trabulsi, Hussam; Al Trabulsi, Dunia; Alrefaie, Khadeja; Muassess, Tala; Guraya, Salman Yousuf (Frontiers in Surgery, 2025)
IntroductionEvidence suggests that hiatal hernia should be repaired if found during laparoscopic sleeve gastrectomy (LSG), either to prevent new-onset post-operative gastro-esophageal reflux disease (GERD), or to treat pre-existing reflux symptoms. There is interest in performing laparoscopic Nissen's fundoplication (LNF) along with hiatal hernia repair (HHR) during LSG. This study aimed to determine whether hiatal crural repair alone is adequate for symptomatic control. We compared operative time, body mass index (BMI), and reflux symptoms between those undergoing LSG with HHR vs. LSG with HHR and LNF.Materials and methodsWe retrospectively analyzed clinical data of patients who underwent LSG with HHR. This cohort was divided into those with LNF (group 1) and without LNF (group 2). We collected patients' pre-operative BMI and GERD Questionnaire (GERD-Q) scores. We then compared pre-operative BMI and GERD-Q values with post-operative indices at 1-month, 3-months, and 6-months. The patients' medical records for operative findings and time between both groups was analyzed. Statistical analyses included Independent Samples T-tests, Paired T-tests, and correlation analysis.ResultsIn this study, 978 bariatric surgeries were performed. Of 431 LSG patients, 73 fulfilled the study criteria. Both groups showed significant reduction in BMI and GERD-Q scores post-operatively. Group 1 had a decrease in BMI from an average pre-operative value of 38.03–32.17 at 6 months (p < 0.001), and GERD-Q scores from 12.25 to 6.47 (p < 0.001). Group 2 showed a BMI decrease from 39.63 to 31.67 (p < 0.001) and GERD-Q scores from 11.54 to 6.93 (p < 0.001) at 6 months. Average operative time was similar in both groups, 76.41 and 79.15 min for group 1 and 2, respectively (p = 0.621).ConclusionOur research with short-term results reports similar improvement in BMI and GERD symptoms in patients with LSG and HHR with or without LNF. A sound repair of hiatal crura combined with LSG leads to comparable outcomes to crural repair combined with LNF and LSG for weight loss and reflux resolution. Our short-term results do not support LNF in combination with LSG and HHR. Further research is essential to determine the long-term outcomes.